Long-distance learning on surgical material sterilization processes - Quelhas, Maria Cristina Ferreira; Lopes, Maria Helena Baena de Moraes; Ropoli, Edilene Aparecida (Revista da Escola de Enfermagem da USP, 2008)
This study had the following goals: describing the development of a distance learning (DL) course on Surgical Material Sterilization Processes, to be given over the Internet; having the course evaluated by specialists in sterilization processes and in DL; describing students' and evaluators' profiles, and to evaluate the students' participation and their opinions about the course. The chosen course environment was TelEduc, and the teaching method was Case-Based Learning. The target population consisted of nurses from the greater Campinas area and other cities of the state of São Paulo. Fifty-eight nurses were invited, 14 were enrolled and 11 finished the course. The course was evaluated by specialists before and after its application. In order to evaluate the students' opinion of the course, a Likert questionnaire was used. The Case-Based Learning methodology helped student participation and the course was evaluated positively.